Investasi Pendidikan Melalui Keikutsertaan Bimbingan Belajar Online: Mampukah Mempengaruhi Hasil Belajar Siswa? - Destin Siti Nur Haliza; Ni'matush Sholikhah (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
One form of household expenditure is in the form of education investment. Investment in education has a good impact on the future of children. Participation in online tutoring is one way for parents to support their child's education. This study aims to determine the effect of student participation in online tutoring on learning outcomes of economics subjects in class XI IPS SMAN 14 Surabaya. This study uses regression analysis techniques with dummy variables. This study resulted in a significant and positive effect of student participation in online tutoring on learning outcomes. The acquisition of student learning outcomes is greater when students participate in online tutoring compared to students who do not take online tutoring.